O paranoico e o laço social: a clínica psicanalítica no tratamento das paranoias - Trinca, Natália Monte (2022)
In this research we will talk about the social bond established in the paranoid subject, through the theoretical-clinical investigation that is developed in the psychoanalytic method. We will discuss the importance of fighting the stigma of the “crazy” in a society, bringing the key point about how psychoanalysis can talk about the subjects of the social, enabling dialogue without distancing the clinical processes from the social. After this explanation, we will bring points about how psychoanalysis can contribute to mental health — and its impasses, since the beginnings of the theory on the notion of subject. We will work with the psychoanalytic contributions since Freud, on psychoanalysis in paranoid subjects, until we reach Lacan and the paranoia. In the work, we will discuss delusion as an attempt to cure, delusional metaphor, substitute, and how all these present mechanisms demonstrate the paranoid subject's attempt to establish a social bond through the stabilization of delusion. We will then bring the notion of what is a social bond and the constitution of society. In the end, we will approach the clinical case, bringing examples of how the subject can establish a social bond, such as emotional bonds and work bonds, through the stabilization of his delusion